Potential of low carbon nanotubes dosage on chromium removal from water - Kabbashi, Nassereldeen Ahmed; Firdaus, Abd-Wahab; Bahaaddin, Warqaa Muhammed; Musa, Lubna Muhamed; Nour, Abdurahman Hamid; Qudsieh, Isam Yasseen (International Islamic University Malaysia-IIUM, 2022)
This paper involves a method of eliminating hexavalent chromium (Cr (VI)) from the synthetic water via a low dosage of carbon nanotubes (CNT). The ability of CNT to remove Cr(VI) from synthetic water through the adsorption process was studied in batch experimentation. The findings revealed up to 100% elimination of Cr(VI) in the 0.07 mg/L Cr(VI) concentration. These excessive elimination proficiencies were credited to the powerful adsorption of chromium ions to the physical properties of the CNT. A pattern layout was created in these experimental runs in order to locate the ideal situation of the Cr(VI) deletion from synthetic water. To accomplish the purposes of the experiment, there were 4 independent variables influencing several points, namely the CNT dosage, the pH of the water, the agitation speed, and the contact time. The StatGraphics Centurion XV software has been used to create the adsorption equivalence and to discover the major impacts to the elimination of Cr(VI). The results show that the adsorption capability of the carbon nanotubes was considerably reliant on the pH of the Cr(VI) solution, supported by the CNT dosage, the contact time, and the agitation speed. The expected optimization, using the adsorption equation, shows that a 1 mg CNT dosage with a pH=2, 120 minutes contact time, and moderate agitation rate at 150 rpm is the most optimal.